Efeito do ângulo de curvatura na homogeneidade microestrutural e de dureza do nióbio puro processado por prensagem em canais equiangulares (ECAP) - Santos, Reinan Tiago Fernandes dos (2023)
Pure niobium specimens were processed by equiangular channel pressing (ECAP) at room temperature in 1 pass, to investigate the effect of lubricants on microstructure, processing variables and hardness homogeneity. In addition, the Nb was deformed in 1, 2, 4, 6 and 8 passes by ECAP, in an ECAP matrix with a straight channel angle (Φ = 90º) using two bending angles (Ψ = 0º and Ψ = 30º). The results showed that the lubricants: anti-seize spray with polytetrafluoroethylene tape, MoS2 grease and MoS2 grease with polytetrafluoroethylene tape showed favorable processing conditions in relation to the ECAP matrix without lubrication. The analysis of the microstructure homogeneity revealed that the banded regions, a random shear flow and the presence of dead zones were determinant in the heterogeneity along the ECAP passes. It is apparent from the analysis of the homogeneity of microstructures and Vickers hardness in the samples, that the angle of curvature had a significant influence up to 4 passes and reducing its effect up to 8 passes. Regarding the homogeneity of hardness, the data do not show variation of Vickers hardness in the two angles of curvature analyzed. After 6 passes, in both matrix configurations, the hardness values were homogeneously distributed along the deformed specimen. The processing of pure Nb by ECAP was efficient to produce a homogeneous microstructure.